Исследование трещиностойкости покрытий TiAlN методом скретч-тестирования.; Физическая мезомеханика; Т. 18, № 6 - Шугуров А. Р. Артур Рубинович; Акулинкин А. А. Александр Александрович; Панин А. В. Алексей Викторович; Сергеев В. П. Виктор Петрович; Калашников М. П. Марк Петрович; Воронов А. В. Андрей Викторович; Cheng Chin-Hsiang (2015, 2015)
Заглавие с экрана